Regulation of human histone gene expression: kinetics of accumulation and changes in the rate of synthesis and in the half-lives of individual histone mRNAs during the HeLa cell cycle. - Heintz, N (1983)
We have analyzed the kinetics of accumulation of each of the individual core histone mRNAs throughout the HeLa cell cycle in cells synchronized by sequential thymidine and aphidicolin treatments. These analyses showed that during the S phase there was a 15-fold increase in the levels of histone mRNAs and that this resulted from both an increased rate of synthesis and a lengthening of the half-life of histone mRNAs. A comparison of the kinetics of accumulation of histone mRNA in the total cellular and nuclear RNA populations suggested an increased transcription rate through the S phase. Within 30 min after the inhibition of DNA synthesis in mid-S phase, the steady-state concentration and the rate of synthesis of histone mRNA each declined to their non-S-phase levels. Reactivation of histone mRNA accumulation could occur even after an extended mid-S-phase block in DNA synthesis. These results suggest that the mechanisms responsible for histone mRNA synthesis are not restricted to the G1/S boundary of the HeLa cell cycle, but can operate whenever DNA synthesis is occurring.